The role of religious and existential spiritual well-being in determining self-care in Jordanian Muslim nursing students - Jehad A. Rababah; Mohammed Munther Al-Hammouri (Social Sciences and Humanities Open)
Spiritual well-being is a major determinant of health. However, evidence regarding the role of spiritual well-being in determining self-care among Muslim nursing students is lacking. This study was conducted to examine the role of spiritual well-being in determining self-care among Muslim nursing students in Jordan. A cross-sectional design was used to conduct this study in a sample of Jordanian Muslim nursing students. Data collection was performed using reliable, valid measures. Bivariate correlations between the dimensions of spiritual well-being and self-care were all statistically significant (r = .28 to .43, p < .001). According to the results of MANOVA and its follow-up analysis, Muslim nursing students who had moderate levels of spiritual, religious, and existential well-being demonstrated lower self-care mean scores compared to those with higher levels of spiritual, religious, and existential well-being. This study provided foundational evidence regarding the integral role of religious, existential, and spiritual well-being in shaping the self-care practices of Jordanian Muslim nursing students.